(untitled) (TAJ: Journal of Teachers Association, 2010)
The incidence of head injuries is growing with greater mechanization in industry and an increase in high velocity transport. The injuries could be caused by a penetrating or blunt force either by direct violence or indirectly, such as a fall on the feet or buttocks. There is no direct relation to the severity of injury to skull bones and extent of cerebral disorder.We is reporting two cases of head injury from forensic point of view. TAJ 2010; 23(1): 98-102